Between Narcissism and Repression: The Castration of Female Desire in Portuguese Film – Julia Kristeva and Abjection, the 1974 Revolution, The Siege and Dina and Django, - Rodrigues, Érica Faleiro (Cinema: Journal of Philosophy and the Moving Image, 2014)
The Portuguese films The Siege (O Cerco, 1970) and Dina and Django (Dina e Django, 1983) are set within divergent socio-political situations: twelve years separate the two, with Portugal’s 1974 revolution and the end to almost fifty years of dictatorship (1926-1974) between them. A man directs The Siege (António da Cunha Teles), while a woman directs Dina and Django (Solveig Nordlund). I depart from Julia Kristeva’s pivotal book Powers of Horror: An Essay on Abjection to ask how two films produced over a decade apart and under different social and political conditions, can both portray women protagonists castrated in the fulfilment of their desire for sexual pleasure and social emancipation — why, in both, these characters progress from narcissism to repression to punishment.